Norpa Signalling and the Seasonal Circadian Locomotor Phenotype in Drosophila - Breda, Carlo (Biology (Basel), 2020)
In this paper, we review the role of the norpA-encoded phospholipase C in light and thermal entrainment of the circadian clock in Drosophila melanogaster. We extend our discussion to the role of norpA in the thermo-sensitive splicing of the per 3′ UTR, which has significant implications for seasonal adaptations of circadian behaviour. We use the norpA mutant-generated enhancement of per splicing and the corresponding advance that it produces in the morning (M) and evening (E) locomotor component to dissect out the neurons that are contributing to this norpA phenotype using GAL4/UAS. We initially confirmed, by immunocytochemistry and in situ hybridisation in adult brains, that norpA expression is mostly concentrated in the eyes, but we were unable to unequivocally reveal norpA expression in the canonical clock cells using these methods. In larval brains, we did see some evidence for co-expression of NORPA with PDF in clock neurons. Nevertheless, downregulation of norpA in clock neurons did generate behavioural advances in adults, with the eyes playing a significant role in the norpA seasonal phenotype at high temperatures, whereas the more dorsally located CRYPTOCHROME-positive clock neurons are the likely candidates for generating the norpA behavioural effects in the cold. We further show that knockdown of the related plc21C encoded phospholipase in clock neurons does not alter per splicing nor generate any of the behavioural advances seen with norpA. Our results with downregulating norpA and plc21C implicate the rhodopsins Rh2/Rh3/Rh4 in the eyes as mediating per 3′ UTR splicing at higher temperatures and indicate that the CRY-positive LNds, also known as ‘evening’ cells are likely mediating the low-temperature seasonal effects on behaviour via altering per 3′UTR splicing.